Test Speed Round at Various Levels of Equipment Type Rotary Roasters Coffee to Quality Products - Lasnita Manurung; Achwil Putra Munir; Lukman Adlin Harahap (Jurnal Rekayasa Pangan dan Pertanian, 2013)
The RPM of coffee roaster mixer tool is needed to care. The machine RPM will affect the roasting quality. Various level of PRM were tested to know the quality of coffee produced. Research had been conducted at agricultural engineering laboratory, faculty Agricultural USU in Juni – September 2012 with using factorial randomized block design with one factor i.e 10, 35,5 and 61 revolution per minute. Parameters observed were organoleptic test, yield, process capacity and water content. The results showed that the RPM had no effect on the organoleptic test, yield and process capacity, and had highly significantly effect on the water content. Key words: Coffee roaster machine, RPM test, Coffee quality